Investigations on size-effect dependent strain and temperature in micro turning near to the cutting edge. Issue 1 (May 2019) - Mandal, Soumen; Hanumaiah, Naga
Abstract: This research presents an investigation for understanding machining physics by assessing temperature and strain near (126 µm) to the cutting edge of tool tip in micro-turning process. Fiber Bragg grating (FBG) sensors were attached near to the cutting edge of the micro-turning tool and experiments with varying depth of cut were conducted to record the strain and temperature simultaneously on an indigenous developed micro-machining centre 'Multi-Fab'. It was observed that with varying depth of cut different mechanisms that is, cutting, ploughing and slipping were dominant due to size-effect. In slipping the temperature and strain fluctuates around a fixed value due to elastic deformation of the work. The recorded strain and rise in temperature during cutting operation were found to be about four times and twice, respectively as compared to ploughing. Material hardness and rate of heat dissipation also play a major role in strain and temperature near to the cutting edge as validated from the experiments. The observations found from the experiments can enable appropriate process control in micro turning by monitoring strain and temperature near to the cutting edge.